Multigrid Method for the Numerical Solution of the Modified Equal Width Wave Equation - Essa, Yasser M. A. (Scientific Research Publishing, 2016)
Numerical solutions of the modified equal width wave equation are obtained by using the multigrid method and finite difference method. The motion of a single solitary wave, interaction of two solitary waves and development of the Maxwellian initial condition into solitary waves are studied using the proposed method. The numerical solutions are compared with the known analytical solutions. Using error norms and conservative properties of mass, momentum and energy, accuracy and efficiency of the mentioned method will be established through comparison with other methods.
Keywords: Multigrid Method; Finite Difference Method; MEW Equation